Online Learning in Nursing Education During the COVID-19 Pandemic: Stress, Satisfaction, and Academic Performance - Oducado, Ryan Michael F; Estoque, Homelo (Institut Ilmu Kesehatan STRADA Indonesia, 2021)
Background: Traditional face-to-face instruction swiftly transitioned into online learning during the global COVID-19 outbreak. Students’ experiences and academic performance in this new learning platform need evaluation.Purpose: The purpose of this research was to determine the undergraduate nursing students’ stress, satisfaction, and academic performance during online learning.Methods: This research was considered a cross-sectional and descriptive-correlational study. The research participants were the second-year undergraduate nursing students from one nursing school in the Philippines. The data were collected using a web-based survey questionnaire and then analyzed using descriptive statistics and Spearman’s rho correlation.Results: The results revealed that the undergraduate nursing students considered having online learning during the COVID-19 outbreak to be stressful (44.4%) and very stressful (47.2%). Moreover, the undergraduate nursing students had low satisfaction (37%) and moderate satisfaction (46.3%) having the online learning during the COVID-19 outbreak. The undergraduate nursing students’ academic performance were affected by the COVID-19 pandemic and resulted in poor (37%) to fair (50%) academic performance and were considerably (43.6%) and greatly (30.6%) affected by the pandemic. Online learning stress had a significant and inverse correlation with online learning satisfaction (p=.000) and academic performance (p=.012).Conclusion: Stress negatively impacts the undergraduate nursing students’ satisfaction and academic performance. This research suggests that certain measures should be performed to reduce stress and improve the online teaching–learning processes during the COVID-19 outbreak.